Study of Novel Punched-Bionic Impellers for High Efficiency and Homogeneity in PCM Mixing and Other Solid-Liquid Stirs - Weitao Zhang (MDPI AG, 2021)
Improvement of stirring performance is one of the primary objectives in solid–liquid mixing processes, such as the preparation of phase change materials (PCMs) for energy saving in refrigeration and heat pump systems. In this paper, three novel impellers are proposed: pitched-blade punched turbine (PBPT), bionic cut blade turbine (BCBT) and bionic cut punched blade turbine (BCPBT). An experimental test was conducted to validate the stirring system model based on the Eulerian–Eulerian method with the kinetic theory of granular flow. Then the performance of the novel impellers was predicted, studied, and compared. The outcomes indicate that a novel impeller, specifically BCPBT, can effectively suspend particles and dramatically reduce power consumption. A better solid–liquid suspension quality was obtained with an aperture diameter of 8 mm and aperture ratio of 13%. Within the range of impeller speeds and liquid viscosity studied in this this paper, higher impeller speeds and more viscous liquids are more conducive to particle dispersion. One of the most important contributions of this work lies in the design of novel impellers, an extent of energy conservation to 17% and efficient mixing was achieved. These results have reference significance for improving the energy efficiency of temperature regulation systems.